Empowerment of SMEs Through Marketing Optimization and Legality Based on the Tourism Potential of the Tandung Andung Reservoir in Lendang Are Village, Central Lombok - Supratman; Afrida Nur Chasanah; Ridho Rafqi Ilhamalimy; Sari Kartikaningrum; Baiq Rabiatul Adawiyah Kartika Wulan (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
Lendang Are Village, located in Kopang Sub-district, Central Lombok Regency, has significant economic potential supported by the micro, small and medium enterprise (MSME) sector and the beauty of Tandung Andung Reservoir tourism. However, MSME players' understanding of digital marketing and business legality is still minimal, hampering their business development. This training aims to improve the understanding of Lendang Are Village MSMEs regarding digital marketing and business legality. The training method consisted of three stages: preparation, implementation, and training with a focus on digital marketing strategies and business legality. The results of the training showed an increase in participants' understanding, especially in utilizing social media and the business legality process. Questionnaire data showed that understanding of digital marketing increased from 40% to 85%, while understanding of business legality increased from 30% to 75%. This training successfully had a positive impact on MSMEs in Lendang Are, especially in preparing them to face a wider market through digital marketing and strong business legality.